Peran Konflik Pekerjaan Keluarga dan Konflik Kerja Emosional Terhadap Kinerja Karyawan Melalui Kepuasan Kerja - Amira Maulidianti; Jul Aidil Fadli (Masyarakat Ekonomi Syariah Bogor, 2025)
Employee performance is a key factor in achieving organizational goals, especially in a dynamic and stressful work environment that can affect employee performance. This study aims to analyze the influence of work-family conflict and emotional labor conflict on employee performance through job satisfaction as a mediating variable. This study was conducted in the Jabodetabek Regional Government. It employed a quantitative approach with a descriptive causal research design. The sample consisted of 100 respondents, selected using purposive sampling with specific criteria. Data collection was conducted through the distribution of a Google Form questionnaire and analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) method. The results of this study indicate that family-to-work conflict and emotional work conflict significantly negatively affect job satisfaction. Additionally, family-to-work conflict has a negative impact on employee performance, while emotional conflict does not directly affect employee performance. On the other hand, job satisfaction is proven to significantly contribute positively to employee performance. Furthermore, job satisfaction acts as a significant mediator in the relationship between independent variables and employee performance. The implications of this study are the importance of organizational strategies in improving work-family role balance and managing emotional aspects in the workplace to create higher job satisfaction. Therefore, organizations are advised to encourage government agencies to design more flexible work policies that support the psychological well-being of female employees.